FAKTOR YANG BERHUBUNGAN DENGAN POLA TIDUR PADA ANAK USIA PRA SEKOLAH YANG MENJALANI HOSPITALISASI - Monalisa Monalisa (NHM PRESS, 2021)
For children, hospitalization creates a crisis in their lives. In the hospital, children have to face an unfamiliar environment, unknown caregivers, and disruption to their lifestyle. This study aims to determine the factors associated with sleep patterns in pre-school age children undergoing hospitalization in the inpatient ward of Raden Mattaher General Hospital, Jambi. This research is an analytic observational study with a cross sectional approach. The population in this study were all children who were hospitalized in the children's room at Raden Mattaher Jambi Hospital, the number of samples in this study was 50 people. Respondents in this study were parents of children who were being treated in the children's room at Raden Mattaher Jambi Hospital, the sampling technique The sample was done by accidental sampling method. This research was conducted in December 2018. The data collection technique was by distributing questionnaires to respondents. The data analysis technique used the chi-square test (< 0.05). The results showed that there was a relationship between physical illness, emotional stress and an uncomfortable environment with the sleep patterns of preschoolers with p-value <0.05. Looking at the results of this study, it is necessary for the cooperation of health workers to meet the client's sleep and rest patterns, especially children undergoing hospitalization.